PENGARUH EDUKASI MELALUI MEDIA E- POSTER TERHADAP PENGETAHUAN REMAJA MENGENAI PENTINGNYA AKTIVITAS FISIK DI KOTA BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: results of research in Indonesia Riskesdas results report in 2018 nationally known there are 33.5% of the population of Indonesia aged more than 10 years less physical activity. As a factor, the reason for a person's lack of physical activity is due to lack of knowledge. If a person does less physical activity can increase the risk of Non-Communicable Diseases. Therefore, it is necessary to increase knowledge with education through e-posters about physical activity. Objective: This study aims to determine the influence of education through e-poster media on adolescent knowledge about the importance of physical activity. Method: this study uses a type of quantitative research with an experimental quasi approach. This research design using one group pre test post test design without control. This study uses nonprobability sampling with a total sampling of 31 students. Univariate analysis with mean and bivariate with paired t test. Results: the average knowledge of adolescents before education was 65.05 and knowledge after education was 77.15 with a difference of 12.1 showed an increase in knowledge from before and after education through e-poster media. In addition, there is the influence of education through e-posters on the knowledge of adolescents about the importance of physical activity in bandung with a value of P= 0.005 <ironic = 0.05. Conclusion: there is the influence of education through the media e-poster on the knowledge of teenagers about the importance of physical activity in Bandung. Recommendation: after knowing and getting information through e-poster media about the importance of physical activity, students are willing and able to apply physical activity in their daily lives, as a form of prevention from Non-Communicable Diseases in the future. Key words: E-poster media, physical activity, knowledge, influence